ANALISA PERBEDAAN KEPUASAN MAHASISWA S1 AKUNTANSI DAN S1 MANAJEMEN SEKOLAH TINGGI ILMU EKONOMI ADI UNGGUL BHIRAWA SURAKARTA - V. Titi Purwantini; Endang Sri Suwarni (STIE AUB Surakarta, 2015)
The aim of this study was to analyze differences Student Satisfaction S1 management and S1 Accounting STIE AUB Surakarta seen from Academic Services, Library Services and laboratory services, with a sample of 100 students, 50 students S1 management and 50 students S1 Accounting Data analysis using the Test Mean Compare Samples t. Results of the study as follows: there is a significant difference between student satisfaction and student management accounting views of academic services. mean difference, each of which is 4813, and 0.80. There are significant differences between student satisfaction and student management accounting views of library services mean difference values are respectively 5.164 and 4.960. no significant differences between student satisfaction and student management accounting views of laboratory services, the mean difference is that each and 4.820 and 1.895 Key words: Academic Services, Library services, Services